For a decolonial clowning (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text intended to address aspects of decoloniality in dialogue with the feminist dramaturgies that contemporary Brazilian clowns have currently created. Through decolonial clowning, we revisit Brazilian colonial heritage, both from a racial and gender perspective. By highlighting aspects of Afro-Brazilian culture, we also sought to decolonize clowning itself, which has the construction of its laughter quite consolidated in a masculinized logic. As examples of decolonial works, we present analyzes of clowning and reflections by gender researchers. In this endeavor, we sought to understand how clowns decolonize their dramaturgies.
Keywords: clowning; decoloniality; gender; feminisms; subversion